Poezie Wilhelma Przeczka v českých a německých překladech - Martinek, Libor (Slavia Occidentalis, 2017)
In this article, we are presenting the work of a Polish poet from a Polish minority the Czech Cieszyn Silesia Wilhelm Przeczek (7. 4. 1936 v Karviná, Czechoslovakia - 10. 7. 2006 Třinec, Czech Republic) into the Czech and German language, as the author’s poetry was published not only in journals but also in books. We understand translation as an expression of intercultural communication, and especially in the area of the literature of a national minority, which is undoubtedly a Polish ethnic group in the Czech Cieszyn Silesia, it is a paramount phenomenon comparing the quality of literary life in the area with majority culture (Czech); as far as translations into German are concerned, it shows the interest of translators in the work of a poet from the Polish national minority, without this witnessing the emanation of a typical Polish soul in Polish literature in the Czech Republic and former Czechoslovakia, but it is evidence that it is fully competitive in total Polish national culture.